THE INFLUENCE OF PRICE, PRODUCT ATTRIBUTES, ORIGIN OF PRODUCT, AND PHILOSOPHY TO CUSTOMER LOYALTY AT PASAR BERIMAN TOMOHON - Runtu, Julia Friny; Tumbuan, Willem J. A. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2015)
Traditional market is a meeting place for sellers and buyers. It is characterized by the presence of sellers and buyer transaction directly and usually a bargaining process happens. Mostly sell daily needs like foodstuffs such as fish, fruit, vegetables, eggs, meat, cloth, clothing, electronic goods, services and others. Additionally, there is also selling pastries and other items. This research is conducted in Pasar Beriman Tomohon. The objectives of this research are to analyze the influence of price, product attributes, origin of product, and philosophy to customer loyalty, partially and simultaneously. This research is the causal type of research where it investigates the influence of price, product attributes, origin of product, and philosophy to customer loyalty. Using a multiple regression model to answer the research problem.Â  The population in this study is a customer of Pasar Beriman Tomohon whereas sample taken by each respondents 100 respondents. The hypothesis testing, this research conduct a conclusion of there is a significant influence of price, product attributes, origin of product, and philosophy to customer loyalty partially and simultaneously.This study reveals that price,product attributes, origin of product; local producthas a strong influence to the customer in order to select, buy and to be a loyal customer at Pasar Beriman Tomohon, they prefer to purchase local products, their perception that local products is better than other products, and become the reason for customer always shop at Pasar Beriman Tomohon. Keywords: price, product attribute, origin of product, philosophy, customer loyalty